Water-land linkages: a relatively neglected issues in integrated water resources management - Bandaragoda, Don Jayatissa (2002)
Water-land linkages are widely acknowledged, and too often assumed, particularly in irrigated agriculture. However, the related resource management issues are either buried in soil science research or sub-merged in water management discourses. Subjects of erosion, degradation, drought and flooding are often discussed as either solely soil-related issues, or purely water-related issues. A commonly accepted definition of IWRM refers to it as "a process, which promotes the coordinated development and management of water, land and related resources" (GWP/TAC, 2000). However, discussions on IWRM often tend to be tilted towards an exclusive treatment of water resource management. One of the reasons for this emphasis is that IWRM has been taken on to a higher plane of analysis, where the preference is given to water policies, water laws and water allocation. The fact that typical management issues are mostly related to interactions between water and land (and other related resources) recedes to the background when water management is viewed simply as an effort in water distribution. The paper proceeds to unpack the concept of IWRM as it has been defined by GWP, and focuses on water-land linkages as far as they seem to be important in a broader view of integrated water resource management. Obviously, the plane in which these interactions take place is the river basin, which, therefore, is the most appropriate unit of analysis for understanding this broader connotation of IWRM. In the promotion of IWRM, an appropriate strategy would be to emphasize on sustainable river basin management.